2002
DOI: 10.2494/photopolymer.15.521
|View full text |Cite
|
Sign up to set email alerts
|

Etch Properties of 193nm Resists: Issues and Approaches.

Abstract: Polymer chemistries for 193nm resists are more or less defined and their lithographic performance is quite good to implement 100nm design rules. In spite of the use of high carbon containing adamantane or norbomene moieties in the polymer design, there exists etch selectivity as well as surface roughness issues after treatment with etch plasma. It is very much necessary to modify the etch plasma used for 193 nm resists to improve the surface roughness. Etch rates of several acrylate, methacrylate and hybrid ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Consistent with our findings, Padmanaban et al 7 compared the surface roughness of different types of 193 nm photoresist in aggressive fluorocarbon plasmas used for oxide etching. They found that electron beam curing of 193 nm photoresist before plasma exposure strongly improved the etch performance of 193 nm photoresist, with regards to both etching rate and introduction of surface roughness.…”
Section: Discussion: Mechanism Of Surface Roughness For 193 Nm Phosupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, Padmanaban et al 7 compared the surface roughness of different types of 193 nm photoresist in aggressive fluorocarbon plasmas used for oxide etching. They found that electron beam curing of 193 nm photoresist before plasma exposure strongly improved the etch performance of 193 nm photoresist, with regards to both etching rate and introduction of surface roughness.…”
Section: Discussion: Mechanism Of Surface Roughness For 193 Nm Phosupporting
confidence: 90%
“…1,2 The decrease of the thickness of 193 nm photoresist materials requires higher plasma etching resistance relative to 248 nm photoresist materials. [5][6][7][8][9][10][11][12][13] In this work, the plasma etching behavior of 193 and 248 nm photoresist is examined in fluorocarbon discharges used for dielectric etching. One issue with 193 nm photoresist materials in plasma etching environments is increased surface roughness as a result of the etch process.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, some groups have studied plasma pre-treatment and VUV/e-beam smoothing effects on 193 nm PR to eliminate LER and LWR [2][3][4][15][16][17][18]. Pargon et al demonstrated that HBr and Ar plasma treatments reduce LWR and attributed the effect to VUV emission (110-210 nm) and low energy ion bombardment [3,4].…”
Section: Introductionmentioning
confidence: 99%